Dimensionamento e simulação de um retificador trifásico controlado para acionamento de um motor de corrente contínua - Sousa, Thiago Pompilio de (Universidade Federal Rural do Semi-Árido, 2019)
Rectifiers are devices used in electronic equipment of our day to day. In addition, these rectifiers on larger scales are widely used in industries. Among these, the oil industry plays a fundamental role for the Brazilian economy and the world economy. Petrorio is an independent oil producer with a focus on investment and recovery of assets in production. In January 2014 Petrorio took over the management of the Polvo field. The Polvo-A platform is located at a distance of 100 kilometers from the city of Cabo Frio in the Campos basin and has the activities of production and drilling of wells. The three-phase three-phase rectifiers used for the drive of the mud pump motors are used in the drilling rig of the Polvo-A platform owned by Petrorio. In this way, the present work consists of analyzing this rectifier in a quantitative and qualitative way, besides proposing solution for the improvement of the energy efficiency of these equipments. Firstly, the single-phase and three-phase controlled rectifiers were analyzed in order to analyze and select the best rectifier to be used in the Polvo-A platform. Thus, during the execution of the work, in possession of the data obtained through calculations and simulations executed in the PSIM program, it was verified that the six-phase controlled three-phase rectifier is oversized, which motivated the elaboration of proposals with improvements to be implemented for this rectifier. Finally, the possible solutions found to improve the efficiency of the rectifiers were studied.
Monografia
Keywords: Retificador; Produção; Perfuração; Trifásicos; Eficiência energética.; ENGENHARIAS::ENGENHARIA ELETRICA